The Differential Role of Narcissism in the Relations Between Childhood Sexual Abuse, Dissociation, and Self-Harm - Talmon, Anat (Journal of interpersonal violence, 2021)
Childhood sexual abuse (CSA) is considered a risk factor for self-harm behaviors. According to the anti-dissociation model of self-harm, the relation between CSA and self-harm is mediated by dissociation. However, inconclusive evidence supporting this model suggests that this association may be moderated by vulnerability factors. Grandiose and vulnerable narcissism represent distinct patterns of behaviors intended to deal with unmet needs of recognition. The aim of the study was to examine a model in which the relation between CSA and self-harm is mediated by dissociation, and the relation between dissociation and self-harm is moderated by grandiose narcissism and vulnerable narcissism. A battery of self-reported questionnaires including the Childhood Trauma Questionnaire, Dissociative Experiences Scale, Deliberate Self-Harm Inventory, and Brief-Pathological Narcissism Inventory were filled out by 766 college/university students. Results indicated that self-harm was related to CSA through the mediation of dissociation. Moreover, the analyses yielded significant interactions of both vulnerable and grandiose narcissism with dissociation in predicting self-harm; the relation between dissociation and self-harm was significant among individuals with high levels of vulnerable narcissism, as well as among individuals with low levels of grandiose narcissism. These findings support the anti-dissociation model of self-harm. The findings also highlight the complex and ambiguous role of narcissism in the long-term adjustment of CSA survivors.